Surface functionalization: an efficient alternative for promoting the catalytic activity of closed shell gold clusters - Joshi, Krati; Krishnamurty, Sailaja; Dar, Manzoor Ahmad (Physical Chemistry Chemical Physics, 2020)
{Surface functionalization through adsorption of ligands or non-metal atoms is considered to be an interesting and viable approach for tuning the physicochemical properties of gold clusters. Highly stable and magic numbered electronic configurations of thiolate protected gold clusters such as Au-25(SR)(18), Au-38(SR)(24)etc. with intriguing properties are the direct manifestation of the rich chemistry of the Au-S interface. The present investigation discerns the CO oxidation activity of structurally well characterized sulphur functionalized gold cluster anions AumS4-